Dynamical analysis of Kaldor business cycle model with variable depreciation rate of capital stock - Junjie Mao; Xiaowei Liu (AIMS Mathematics, 2020)
In this paper, the Kaldor business cycle model with variable depreciation rate of the capital stock are investigate the existence, uniqueness and stability of the positive equilibrium point, and the existence of the periodic solution and Hopf bifurcation respectively. Finally, we analyze the dynamic behaviors of the specific system and perform numerical simulations.